2020
DOI: 10.1038/s41598-020-60024-3
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive carbon improves nitrogen fertiliser efficiency and ecological sustainability

Abstract: Agriculture's most pressing challenge is raising global food production while minimising environmental degradation. Nutrient deficiencies, principally nitrogen (N), limit production requiring future increases in fertiliser use and risk to proximal non-agricultural ecosystems. We investigated combining humate with urea, globally the most widely used N-suppling fertiliser, in a four-year field study. Humate increased pasture yield by 9.8% more than urea and significantly altered soil microbial diversity and func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…The yield responses to humate in this trial were similar to the 9% -14% increases reported in other ryegrass -white clover pastures in New Zealand 49,60 . The principal pasture grasses in this trial, perennial and Italian ryegrass (Lolium perenne L and L. multi orum L), and other legumes have been shown to positively respond to humates 61,62 .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The yield responses to humate in this trial were similar to the 9% -14% increases reported in other ryegrass -white clover pastures in New Zealand 49,60 . The principal pasture grasses in this trial, perennial and Italian ryegrass (Lolium perenne L and L. multi orum L), and other legumes have been shown to positively respond to humates 61,62 .…”
Section: Discussionsupporting
confidence: 80%
“…Despite this, and ready commercial availability, they have not been widely used in commercial agriculture. This is partly attributable to uncertainty regarding modes of action, inconsistent or inhibitory results, and the scarcity of conclusive long-term eld evidence 35,48,49 . .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, favourable prospects for the use of such interactions are documented throughout the literature (Gaba et al, 2015). They typically involve many levels, from soil‐based interactions involving soil microbiota (e.g., Nkongolo & Narendrula‐Kotha, 2020), tripartite soil–plant interactions (namely intercropping, e.g., Tilman, 2020) and biomass cycling and increased soil health and fertilization (Espie & Ridgway, 2020). They may also rely on crop diversity as a way to control disease spread (Boudreau, 2013) and pest populations (Dively et al, 2020), including recourse to parasitoids, specific push–pull strategies aiming to trap pests out of crops (D'Annolfo et al, 2021), and even multiline varietal strategies to contain and slow down diseases within fields (Wuest, Peter, & Niklaus, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, favourable prospects for the use of such interactions are documented throughout the literature (Gaba et al, 2015). They typically involve many levels, from soil-based interactions involving soil microbiota (e.g., Nkongolo & Narendrula-Kotha, 2020), tripartite soil-plant interactions (namely intercropping, e.g., Tilman, 2020) and biomass cycling and increased soil health and fertilization (Espie & Ridgway, 2020). They may also rely on crop diversity as a way to control disease spread…”
mentioning
confidence: 99%
“…It is worthy to note, however, that adsorption is a crucial mechanism in the preparation of slow release fertilizers [4], which may explain why the vast majority of the biocharbased fertilizers have been formulated with salts containing charged elements such as ammonium, nitrate, phosphates, K, etc. However, since urea is the most widely used nitrogen fertilizer in the world [15,16], its efficient management (checking its inordinate release into the environment) is of utmost importance for both agricultural productivity and environmental quality [17].…”
Section: Introductionmentioning
confidence: 99%